2013
DOI: 10.2215/cjn.10671012
|View full text |Cite
|
Sign up to set email alerts
|

Association of Left Ventricular Longitudinal Strain with Mortality among Stable Hemodialysis Patients with Preserved Left Ventricular Ejection Fraction

Abstract: SummaryBackground and objectives Little is known about the optimal echocardiographic parameters for risk stratification in stable dialysis patients with preserved left ventricular ejection fraction (LVEF) (ejection fraction $50%). Left ventricular (LV) global peak systolic longitudinal strain (GLS) is the ratio of the maximal change in myocardial longitudinal length in systole to the original length and reliably and accurately assesses LV function. During systole, LV myocardium in the longitudinal direction sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(113 citation statements)
references
References 38 publications
7
101
0
5
Order By: Relevance
“…The more recent application of strain analysis has confirmed the prognostic value when the EF is preserved, supporting that the EF may not have been the optimal primary cardiac imaging-based outcome (30,31). In this trial there was a clear and consistent signal of both preservation of function directly measured by LV strain and inferred from reductions in LV mass and LV dilation that the cooling intervention was effective at protecting the heart.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The more recent application of strain analysis has confirmed the prognostic value when the EF is preserved, supporting that the EF may not have been the optimal primary cardiac imaging-based outcome (30,31). In this trial there was a clear and consistent signal of both preservation of function directly measured by LV strain and inferred from reductions in LV mass and LV dilation that the cooling intervention was effective at protecting the heart.…”
Section: Discussionmentioning
confidence: 68%
“…Several studies in patients on HD showed an independent association of changes in LV mass with cardiovascular mortality (28,29). Recent studies determined that systolic strain and diastolic dysfunction predicted all-cause mortality or cardiovascular events in patients on HD with a normal EF (30,31). Both HD and non-HD population studies show that aortic distensibility independently predicts future cardiovascular events (22,32).…”
Section: Rationale For Study Outcomesmentioning
confidence: 99%
“…57 Recently, Liu et al reported that global longitudinal strain is an independent predictor of all-cause mortality in patients with ESRD who have preserved left ventricular function. 58 Although radial, circumferential, and longitudinal fibers are predominantly in different layers of the myocardium, we observed reduced myocardial deformation in all these orientations when we compared our ESRD patient cohort to healthy persons. As heart muscle is incompressible, strain parameters are interrelated in three dimensions; thus, by the time the chamber contracts and shortens in systole (circumferential and longitudinal strain), the wall thickens (radial strain).…”
Section: Discussionmentioning
confidence: 72%
“…Studies performed in adults with hypertension with speckle tracking technology have suggested that abnormalities in systolic performance in hypertensive LV hypertrophy can be identified, despite normal ejection fraction (18)(19)(20). Subclinical abnormalities of LV myocardial deformation in adults with early stage CKD have also been reported (21) as well as abnormal longitudinal systolic deformation in asymptomatic individuals with early CKD without clinical evidence of heart disease.…”
Section: Introductionmentioning
confidence: 99%